Utilization of follow-up care facilities by patients with chronic renal failure attending GH Anuradhapura and DH Medawachchiya - Ranaweera, K.D.N.P (My University, 2007)
Objective of the study was to study the utilization of follow-up care facilities by CRF patients with a view of identifying constrains and recommendations to improve utilization of renal clinic (Re) facilities. 436 diagnosed patients with CRF attending RC GHA and RC DHM were selected for the study. Pre-tested questionnaire was administered to patients by interviewers. Observation check list was used to assess the available facilities at RC DHM. Among CRF patients attending RC GHA and RC DHM majority (28.2 percent ) were from Medawachchiya MOH area. Mean age of CRF patients attending RC was 55.36 years. 58.3 percent of patients attending RC were males. 52.3 percent of CRF patients travel more than 20 kilo meters to attend RC. Majority of CRF patients attending RC were farmers in low socio economic class. Patients attending RC DHM spent more time for traveling than patients attending RC OHA. Waiting time for doctors at RCDHM was higher than that of RC OHA. Waiting time at the dispensary by patients attending RC OHA is more than that of RC DHM. CRF patients of RC OHA spent more money for transport and laboratory investigations than patients attending RC DHM